2013
DOI: 10.4103/0974-777x.107172
|View full text |Cite
|
Sign up to set email alerts
|

Hemoperitoneum in dengue fever with normal coagulation profile

Abstract: A 43-year-old male living in Bengaluru sought emergency services due to high-grade fever, headache, myalgia, abdominal pain and distension. Platelet count (except the first-96,000/mm3) and coagulation profile was in normal limits. The dengue serology was positive for IgM and Ig G (immunoglobulin M and G) antibodies. Ultrasound abdomen showed gross ascites, mild bilateral pleural effusion and hepatosplenomegaly. The patient continued to have abdominal pain and progressive distention Ascitic tap was hemorrhagic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…2 In women with Dengue fever, associated thrombocytopenia further increases the chances of spontaneous hemoperitoneum in luteal phase of menstrual cycle. 6 Diagnosis may be difficult due to multiple conditions mimicking its presentation like acute appendicitis, rupture ectopic pregnancy, acute urinary tract infection etc. Prompt diagnosis (specially using ultrasound), negative urine pregnancy test, other blood biochemical investigations and eventually surgical management are mainstay of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In women with Dengue fever, associated thrombocytopenia further increases the chances of spontaneous hemoperitoneum in luteal phase of menstrual cycle. 6 Diagnosis may be difficult due to multiple conditions mimicking its presentation like acute appendicitis, rupture ectopic pregnancy, acute urinary tract infection etc. Prompt diagnosis (specially using ultrasound), negative urine pregnancy test, other blood biochemical investigations and eventually surgical management are mainstay of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing factors for the same are (a) hemoconcentration, (b) increased prothrombin time, (c) elevated alanine transaminase (ALT) and (d) platelet count of less than 50,000 cells/mm 3 . 6 In literature, There are few case reports of dengue illness with hemoperitoneum secondary to spontaneous rupture of the spleen. 6 corpus luteal cyst rupture has been discussed commonly as radiological differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent report from Malaysia, Ng et al concluded that "early surgical intervention in perforated gastric ulcer is vital in preventing further complication and reducing the risk of mortality (7)." In case with suspicious hemoperitoneum due to dengue, the laparoscope approach is also reported as a safe diagnostic approach (8). In order to select a minimally invasive surgery in dengue patient, several considerations, especially patient's condition are important.…”
mentioning
confidence: 99%